A little book of sloth - Cooke, Lucy, 1970- (New York : Margaret K. McElderry Books, 2013)
Information on habits, habitats, eating habits, and behavior accompany adorable photographs of baby sloths.
AD 870
Keywords: Sloths -- Juvenile literature; Sloths -- Costa Rica -- Juvenile literature